Structures of fluoro, amino, and thiol inhibitors bound to the [Fe 4S4] protein IspH - Span, Ingrid; Wang, Ke; Wang, Weixue; Jauch, Johann; Eisenreich, Wolfgang; Bacher, Adelbert; Oldfield, Eric; Groll, Michael (Angewandte Chemie International Edition, 2013)
The iron-sulfur protein IspH catalyzes a key step in isoprenoid biosynthesis in bacteria and malaria parasites. Crystal structures of IspH complexed with three substrate analogues reveal their mode of binding and suggest new routes to inhibitor design. Copyright © 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.
CRIS-Team Scopus Importer:2021-09-24
Keywords: bioinorganic chemistry; IspH; LytB; metalloenzymes; terpenoids